ADAM12 is a prognostic factor associated with an aggressive molecular subtype of high-grade serous ovarian carcinoma. (29th April 2015) - Cheon, Dong-Joo; Li, Andrew J.; Beach, Jessica A.; Walts, Ann E.; Tran, Hang; Lester, Jenny; Karlan, Beth Y.; Orsulic, Sandra
Abstract: ADAM metallopeptidase domain 12 (ADAM12) is a promising biomarker because of its low expression in normal tissues and high expression in a variety of human cancers. However, ADAM12 levels in ovarian cancer have not been well characterized. We previously identified ADAM12 as one of the signature genes associated with poor survival in high-grade serous ovarian carcinoma (HGSOC). Here, we sought to determine if high levels of the ADAM12 protein and/or messenger RNA (mRNA) are associated with clinical variables in HGSOC. We show that high protein levels of ADAM12 in banked preoperative sera are associated with shorter progression-free and overall survival. Tumor levels of ADAM12 mRNA were also associated with shorter progression-free and overall survival as well as with lymphatic and vascular invasion, and residual tumor volume following cytoreductive surgery. The majority of genes co-expressed with ADAM12 in HGSOC were transforming growth factor (TGF)β signaling targets that function in collagen remodeling and cell–matrix adhesion. In tumor sections, the ADAM12 protein and mRNA were expressed in epithelial cancer cells and surrounding stromal cells. In vitro data showed that ADAM12 mRNA levels can be increased by TGFβ signaling and direct contact between epithelial and stromal cells. High tumor levels of ADAM12 mRNA were characteristic of the mesenchymal/desmoplastic molecular subtype of HGSOC, which is known to have the poorest prognosis. Thus, ADAM12 may be a useful biomarker of aggressive ovarian cancer for which standard treatment is not effective. Summary: Elevated ADAM12 is a prognostic factor associated with adverse clinical outcomes in high-grade serous ovarian carcinoma. ADAM12 is highly expressed in tumor epithelial cells and adjacent stromal cells and is associated with the mesenchymal/desmoplastic molecular subtype of ovarian cancer.